Academic perception of barriers to the adoption of technological innovations during the covid-19 pandemic - Verónica García Martínez; Martha Patricia Silva Payró (Universidad de Guadalajara, 2022)
The objective of this research was to identify barriers to the adoption of a technological innovation perceived by professors at a public university in southeastern Mexico, in which a strategy for the use of virtual classrooms was implemented as a measure to address the social distancing forced by the covid-19 pandemic. A descriptive, non-experimental, cross-sectional, quantitative descriptive study was carried out in which two groups of incident factors were considered: intrinsic (attitudes and beliefs; knowledge and skills) and extrinsic (available resources and educational system). A questionnaire with 30 items was designed and measured with a Likert-type scale and applied to 805 teachers. The results showed that teachers perceive extrinsic barriers as the most important in adopting technological innovations, especially those related to equipment and connectivity, while intrinsic barriers are are mainly focused on the beliefs, so the early adopters and early majority profiles are distinguished.